2020
DOI: 10.1016/j.icarus.2019.113437
|View full text |Cite
|
Sign up to set email alerts
|

Positive ion chemistry in an N2-CH4 plasma discharge: Key precursors to the growth of Titan tholins

Abstract: Titan is unique in the solar system as it hosts a dense atmosphere mainly made of molecular nitrogen N 2 and methane CH 4 . The Cassini-Huygens Mission revealed the presence of an intense atmospheric photochemistry initiated by the photo-dissociation and ionization of N 2 and CH 4 . In the upper atmosphere, Cassini detected signatures compatible with the presence of heavily charged molecules which are precursors for the solid core of the aerosols. These observations have indicated that ion chemistry has an imp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…In some laboratory simulations of the chemical processes occurring in the atmosphere of Titan, the abovementioned precursor ions, as predicted using calculated models, were detected. Dubois et al (2020) [94] shown in reaction 2. These laboratory data are consistent with the above-cited model calculations [93].…”
Section: Constituentmentioning
confidence: 96%
See 1 more Smart Citation
“…In some laboratory simulations of the chemical processes occurring in the atmosphere of Titan, the abovementioned precursor ions, as predicted using calculated models, were detected. Dubois et al (2020) [94] shown in reaction 2. These laboratory data are consistent with the above-cited model calculations [93].…”
Section: Constituentmentioning
confidence: 96%
“…The results of Dubois et al (2020) [94] show that discharge plasma can be used in laboratory studies to explore the chemistry of the atmosphere of Titan. Although the recent improvements in photochemical modeling [34,95] have increased our understanding of the chemical processes that occur in the atmosphere of Titan, we still lack considerable information regarding the specific chemical pathways that result in the production of organic aerosols.…”
Section: Constituentmentioning
confidence: 99%
“…The species of the gas mixture were then irradiated by a windowless EUV photon source coupled to the photochemical reactor produced by a microwave plasma discharge of a lowpressure inert neon flux providing radiation at 73.6 nm (NeI resonance line), corresponding to a photon energy of 16.8 eV, for a flux of about 10 14 ph cm −2 s −1 (Tigrine et al 2016;Bourgalais et al 2019). The photoproducts present in the reactor were then sampled using a quadrupole m/z spectrometer (Hiden Analytical EQP 200 QMS) to measure neutral compounds and positive ions with high sensitivity below the parts per million (ppm) level (Bourgalais et al 2019;Dubois et al 2019Dubois et al , 2020. It is worth noting that the neutral molecules detected in this article are A171, page 2 of 9 ionized fragments.…”
Section: Uv Irradiation Of Simplified Exoplanetary Atmosphere Reproduced In the Laboratorymentioning
confidence: 99%
“…Several studies actually considered the chemical activation via plasma electron of planetary atmospheric compositions with a prebiotic perspective. For example, plasma chemistry has been studied in electric discharges fed with chemical compositions compatible with the present atmosphere of Titan [ 44 , 45 , 46 , 47 , 48 ] and for Venus and Jupiter atmospheres [ 49 ].…”
Section: Introductionmentioning
confidence: 99%